Фармакологічна корекція HSP70-залежної системи ендогенної нейропротекції після хронічної пренатальної гіпоксії - Алієва, Олена Геннадіївна; Бєленічев, Ігор Федорович; Тишкін, С. М.; Риженко, О. І.; Alieva, O. G.; Belenichev, I. F.; Tishkin, S. M.; Ryzhenko, O. I. (My University, 2023)
Мета дослідження – оцінити вплив таких засобів, як ангіолін, пірацетам, тіотриазолін, нікомекс, цереброкурин, тамоксифен, L-аргінін, глутаредоксин, HSF-1 і мілдронат на експресію білка HSP70 та виживання потомства після ХПГ. Дослідження проводили на 50 самках білих лабораторних щурів, в яких моделювали хронічну гемічну нітрит-індуковану пренатальну гіпоксію. Вагітним самкам щурів щодня підшкірно вводили розчин нітриту натрію в дозі 50 мг/кг з 16 до 21 доби вагітності. Вагітним самкам контрольної групи вводили фізіологічний розчин у тому самому режимі. Потомство було поділено на групи: 1 − інтактні; 2 − контрольна після ХПГ; 3 – ХПГ + ангіолін (50 мг/кг); 4 – ХПГ + пірацетам (500 мг/кг); 5 – ХПГ + тіотриазолін (50 мг/кг); 6 – ХПГ + нікомекс (100 мг/кг); 7 – ХПГ + цереброкурин (150 мкл/кг); 8 – ХПГ + тамоксифен (0,1 мг/кг); 9 – ХПГ + L-аргінін (200 мг/кг); 10 – ХПГ + глутаредоксин (200 мкг/кг); 11 – ХПГ + HSF-1 (50 мг/кг); 12 – ХПГ + мілдронат (50 мг/кг). Усі препарати вводили новонародженим щурам протягом 30 діб у терапевтично ефективних дозах, запозичених з літератури. The aim of the study – to evaluate the effects of such agents, as angiolin, piracetam, thiotriazoline, nicomex, cerebrocurin, tamoxifen, L-arginine, glutaredoxin, HSF-1 and mildronate on HSP70 expression and offspring survival after CPH. Studies were conducted on 50 female white laboratory rats with modeled chronic hemic nitrite-induced prenatal hypoxia. Pregnant female rats received daily subcutaneous injection of sodium nitrite solution at a dose of 50 mg/kg from 16 to 21 days of gestation. Pregnant females of the control group were administered saline solution according to the same regimen. The offspring were divided into groups: 1 – intact; 2 – control after CPH; 3 – CPH + angiolin (50 mg/kg); 4 – CPH + piracetam (500 mg/kg); 5 – CPH + thiotriazoline 50 mg/kg); 6 – CPH + nicomex (100 mg/kg); 7 – CPH + cerebrocurine (150 μl/kg); 8 – CPH + tamoxifen (0.1 mg/kg); 9 – CPH + L-arginine (200 mg/kg); 10 – CPH + glutaredoxin (200 μg/kg); 11 – CPH + HSF-1 (50 mg/kg); 12 – CPH + mildronate (50 mg/kg). All drugs were administered for 30 days at therapeutically effective doses borrowed from the literature. It was found that CPH causes a decrease in the level of HSP70 in brain tissue and blood plasma and increases offspring mortality. A direct correlation between HSP70 level and offspring survival has been established. Administration of angiolin, piracetam, thiotriazolin, nicomex, L-arginine, glutaredoxin, tamoxifen, mildronate, HSF-1 and cerebrocurin during the first 30 days of rat life after CPH exposure leads to an increase in HSP70 level, which demonstrates the neuroprotective properties of these drugs. Angiolin (50 mg/kg), cerebrocurin (150 ml/kg) and HSF-1 (50 mg/kg) are the most effective drugs in terms of their ability to influence HSP70-dependent mechanisms of endogenous neuroprotection among the investigated agents after CPH modeling, surpassing other drugs by the level of increase in HSP70 concentration in brain tissue and blood plasma and also by the offspring survival.
Pharmacological correction of HSP70-dependent endogenous neuroprotection system after chronic prenatal hypoxia
Keywords: хронічна пренатальна гіпоксія; білок теплового шоку HSP70; нейропротекція; фармакологічна корекція; chronic prenatal hypoxia; brain; blood; heat shock protein HSP70; neuroprotection; cereb-rocurin; angiolin; nicomex; tamoxifen; thiotriazoline; glutaredoxin; L-arginine; mildronate; pharmacological correction